3Economic Criticism. (27th June 2018) - Crosthwaite, Paul; Knight, Peter; Marsh, Nicky
Abstract: This chapter covers recently published work in economic criticism, exploring the interplay in this scholarship between contemporary and historical frames and the methodological approaches of economics and the humanities. It is divided into four sections: 1. Introduction; 2. Narrating the Economy; 3. Economic Histories and Cultures; 4. Economic Humanities.